Therapeutic proteins have the potential to become new weapons in the fight against antibiotic resistance - Halawa, Mohamed; Akantibila, Maxwell; Reid, Briana E.; Carabetta, Valerie J. (Frontiers in Bacteriology, 2023)
Humans are continually challenged to find new strategies to fight bacterial diseases due to the global health threat of antibiotic resistance. Conventional antibiotics, once hailed as miracle treatments, are progressively losing their effectiveness as drug-resistant bacteria continue to emerge, including multidrug-resistant (MDR) strains. An attractive approach to solving the antibiotic resistance problem is the investigation of other methods, such as therapeutic proteins. Here, we begin with a discussion of antimicrobial resistance and common strategies that bacteria employ to become resistant. Next, we discuss the potential use of antimicrobial peptides and monoclonal antibodies, two types of therapeutic proteins, as possible antimicrobial therapeutics. We discuss their structure, mechanism of action, and highlight examples of possible candidate molecules for clinical use. Finally, we discuss the remaining challenges and explore potential solutions for the implementation of therapeutic proteins into practical clinical use.